The rise of decentralized finance (DeFi): Opportunities for disruption in traditional financial models - I Gede Wahyu Antara Kurniawan; Made Sudiarta; Luh Mei Wahyuni; Ida Ayu Ketut Sumawidari; Kasiani Kasiani; Maria Bernadetha; Muhammad Zulfan; Firman Sinaga (Journal of Education, Social & Communication Studies, 2025)
The rise of Decentralized Finance (DeFi) represents a transformative shift in the global financial landscape, challenging traditional financial models and offering new possibilities for a more inclusive and efficient financial system. This study aims to explore the opportunities and challenges that DeFi poses to the conventional financial sector, focusing on its impact on banking, credit systems, investments, and payment systems. A mixed-methods approach was employed, including secondary data analysis, expert interviews, and first-hand experience with DeFi protocols such as lending, borrowing, and arbitrage. The findings highlight the significant potential of DeFi in creating alternative financial models that can increase financial inclusion, enhance access to capital, and reduce transaction costs. Recent data indicates that the Total Value Locked (TVL) in DeFi platforms has surged to over $50 billion as of January 2025, reflecting growing adoption. Additionally, daily transaction volumes across major DeFi platforms have reached approximately $10 billion, with active users exceeding 4 million globally. However, the research also identifies critical challenges, including regulatory uncertainty, security vulnerabilities, and the complexity of DeFi platforms, which pose barriers to mainstream adoption. This paper contributes to the understanding of how DeFi can reshape the financial ecosystem, offering insights into its future potential, the risks involved, and the steps required to address the existing challenges. Furthermore, it underscores the need for ongoing research into the regulatory aspects of DeFi and its collaboration with traditional financial institutions.